2023
DOI: 10.1186/s12903-023-02803-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of muco-adhesive tacrolimus patch on caspase-3 induced apoptosis in oral lichen planus: a randomized clinical trial

Abstract: Background The study compared the clinical effectiveness of topical Tacrolimus (TAC) in patches or gel with Triamcinolone acetonide (TRI) gel for erosive/atrophic oral lichen planus (OLP) and investigated the influence of these therapies on Caspase-3 expression as a marker of apoptosis. Methods Thirty patients were randomly assigned into three equal groups to receive either topical TAC 0.1% patch twice daily, topical TAC 0.1% gel, or topical TRI 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…A 5-year trial found that Tacrolimus inhibited lesion progression and improved subjective complaints ( Utz et al., 2022 ). Another study found that the tacrolimus group showed increased mesenchyme expression of the apoptosis marker caspase-3, which may indicate impaired T-cell viability and reduce local inflammation, explaining its role in OLP immunology ( Ibrahim et al., 2023 ). However, one of the side effects of tacrolimus is that topical application of tacrolimus can release neuropeptides such as substance P to stimulate sensory neurons and produce a transient burning or painful sensation ( Riano Arguelles et al., 2006 ).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…A 5-year trial found that Tacrolimus inhibited lesion progression and improved subjective complaints ( Utz et al., 2022 ). Another study found that the tacrolimus group showed increased mesenchyme expression of the apoptosis marker caspase-3, which may indicate impaired T-cell viability and reduce local inflammation, explaining its role in OLP immunology ( Ibrahim et al., 2023 ). However, one of the side effects of tacrolimus is that topical application of tacrolimus can release neuropeptides such as substance P to stimulate sensory neurons and produce a transient burning or painful sensation ( Riano Arguelles et al., 2006 ).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…These mucodhesive patches successfully extended the residence time of the patch in the oral cavity to 3-10 h based on the improved structural stability and multiple interactions with mucosal tissue, which effectively improved the release efficiency of the therapeutic drugs, cytokines and proteins at the site of mucosal injury. In particular, several studies have shown good therapeutic effects on human volunteers and clinical trials have been carried out, which are very encouraging 19,20 , However, most of these oral mucoadhesive patches often require complex preparation techniques. In addition, they lack intrinsic therapeutic efficacy, and exogenous drugs, cytokines or proteins load will increase the cost of the patch or may cause potential drug toxicity.…”
mentioning
confidence: 99%